Effects of dipping into anti-browning solutions on the colour changes of minimally processed shredded cabbage - Ibrahim, Roshita; Osman, Azizah; Saari, Nazamid; Abdul Rahman, Russly (2001)
The shelf life of minimally processed fruits and vegetables is often limited by enzymatic browning. The organoleptic properties of fruits and vegetables are strongly altered by the appearance of brown pigments. Therefore this study was conducted to determine the effect of dipping into anti browning solutions namely 0.1% sodium metabisulphite and 0.1% acetic acid on the colourchanges of minimally processed shredded cabbage stored at chilled temperature. 5±1 't'; 90-95% RH and packed in polymeric film, polypropylene. Shredded cabbage dipped in distilled water was used as control. The colour changes was assayed quantitatively using Hunter Lab colorimeter at weekly interval The results obtained showed that 0.1% sodium metabisulphite gave slightly better colour retention than 0.1% acetic acid. However, 0.1% acetic acid can also be considered as one of good alternatives to sulphites in retaining the colour of low temperature storage shredded cabbage.